Perlindungan Hukum Bagi Pemenang Lelang yang Barangnya Masih Dimiliki Debitur Dikaji Menurut Undang-Undang No. 4 Tahun 2004 Tentang Lelang - Fikri Ahmad Anwari; Alexander Triastanto; Ummi Maskanah (Universitas Djuanda, 2025)
This research discusses the legal protection for auction winners whose items are still held by the debtor, analyzed based on Law Number 4 of 2004 on Auctions. An auction is one of the ways to enforce the rights of creditors against debtors who are unable to fulfill their obligations. In this study, the author examines the provisions in Law Number 4 of 2004 as well as the applicable legal practices to provide an overview of the legal steps that auction winners can take to obtain the items they have won. The research findings indicate that although the auction winner has the right to the items once the auction process is complete, there is a legal protection mechanism that must be followed to obtain those items, including through the execution of goods by the auction official. This study also highlights the importance of legal protection for auction winners so that their ownership rights over the auctioned items can be effectively protected in accordance with the applicable procedures.